Eco-Friendly Transformation and Energy Efficiency in Methanol-to-Olefins (MTO) Processes: Innovations Toward Sustainable Olefin Production - Heriyanto, Heri; Rochmat, Agus; Suhendi, Endang; Pujiastuti, Hendrini; Wardalia, Wardalia; Kanani, Nufus (World Chemical Engineering Journal, 2024)
Uncertainty regarding global crude oil prices has raised concerns for industry players, including the intermediate chemical industry such as olefins. The possibility of oil prices rising unpredictably makes the production of olefins from naphtha less attractive. On the other hand, abundant reserves of coal and natural gas are being considered as the foundation for developing the olefin industry based on gasification processes. The process routes include the formation of synthetic gas (SynGas) consisting of Hydrogen and Carbon Monoxide (H2 and CO), Methanol production from SynGas, and Olefin production from Methanol (MTO). This review aims to provide an overview of MTO and future developments related to the diversification of processes and technologies for the commercial production of olefins. Current research development on the Methanol-to-Olefins (MTO) process has narrowed down to three main areas, including: (1) Catalyst modification to increase reaction yield (particularly C2 and C3 products), (2) Determination of detailed reaction mechanisms in olefin formation, and (3) Catalyst deactivation processes in MTO.